Expression of Piezo1 in the Trigeminal Neurons and in the Axons That Innervate the Dental Pulp - Cho, Yi Sul; Han, Hye Min; Jeong, Soon Youn; Kim, Tae Heon; Choi, So Young; Kim, Yun Sook; Bae, Yong Chul (Frontiers in Cellular Neuroscience, 2022)
Information on the neurons and axons, which express the mechanosensitive channel Piezo1 and its expression in axons innervating the dental pulp may help understand the nature of the Piezo1-mediated mechanosensation and the underlying mechanism of dentin sensitivity elicited by mechanical stimuli. For this, we here investigated the neurochemical properties of the neurons in the rat trigeminal ganglion (TG) and their axons in its sensory root that express Piezo1, and the expression of Piezo1 in the rat and human dental pulp by light and electron microscopic immunohistochemistry and quantitative analysis. Piezo1 was expressed mainly in medium-sized and large TG neurons. Piezo1-immunopositive (+) neurons frequently coexpressed the marker for neurons with myelinated axons, NF200 but rarely the markers for neurons with unmyelinated axons, CGRP or IB4. In the sensory root of TG, Piezo1 was expressed primarily in small myelinated axons (Aδ, 60.2%), but also in large myelinated (Aβ, 24.3%) and unmyelinated (C, 15.5%) axons. In the human dental pulp, Piezo1 was expressed in numerous NF200+ axons, which formed a network in the peripheral pulp and often “ascended” toward the dentin. Most Piezo1+ myelinated axons in the radicular pulp became unmyelinated in the peripheral pulp, where Piezo1 immunoreaction product was associated with the axonal plasma membrane, suggesting a functional role of Piezo1 in the peripheral pulp. These findings suggest that Piezo1 is involved primarily in mediating the acute pain elicited by high threshold mechanical stimuli, and that the Piezo1-mediated dental mechanotransduction occurs primarily in the axons in the peripheral pulp.